As "regras" como instrumento interpretativo da filosofia cartesiana - Ana Cláudia Teodoro Sousa (2024)
The Rules for the Direction of the Mind (1628?) is an unfinished text dating from the early years of René Descartes (1596-1650). This work has an epistemological and methodological character. It is the lengthiest and most detailed exposition of Descartes’s method, one of the most distinctive elements of his philosophy. However, the abandonment and incompleteness of this treatise raise several questions and lead to a wide range of hypotheses regarding its construction, dating, intentions, shortcomings, and, most importantly, its place within Cartesian philosophy. The aim of the present work is to defend the thesis of the continuity of Cartesian thought, arguing that it is possible to resort to the Rules for the Direction of the Mind as a support for the interpretation and understanding of Descartes' mature philosophy. In this context, we also consider the embryonic nature of the doctrines and views presented in the abandoned text. To do so, we use the Rules themselves as the guiding thread of this study, analyzing the main themes presented there by Descartes and bringing them closer to what the philosopher wrote about the same topics in his maturity. Thus, we offer a panorama that elucidates which aspects of the Rules were retained by Descartes within later in his intellectual journey, while also revealing which themes were set aside, replaced, or further developed. We conclude that the Rules for the Direction of the Mind, far beyond being a mere explanation of the Cartesian method, provide essential content for understanding Cartesian philosophy as a whole. The study of this treatise reveals the 'first seeds' of Descartes' thought, exposing how the young philosopher initially grappled with problems that would accompany him throughout his philosophical, methodological, and scientific journey.